A comparison of different treatment managements in patients with acute deep vein thrombosis by the effects on enhancing venous outflow in the lower limb - Rahman, Ali; Colak, Mehmet Cengiz; Ustunel, Latif; Koc, Mustafa; Kocakoc, Ercan; Colak, Cemil (Int Scientific Information, Inc, 2009)
Background: This study aimed at evaluating the benefits of the traditional management of acute deep vein thrombosis (DVT), subcutaneous (sc) administration of low-molecular-weight heparin (LMWH) one dose a day and bed rest, and LMWH with compression stocking and early ambulation compared with LMWH with pneumatic compression (PC) in patients with DVT. Material/Methods: Forty-eight consecutive patients with DVT were separated evenly into four groups. Group A received intravenous unfractionated heparin, group B received sc injection of enoxaparin sodium and bed rest, group C received sc injection of enoxaparin sodium and thigh-length compression stockings, and group D received sc injection of enoxaparin sodium and PC for periods of up to 7 days. Results: Comparing days 0 and 7, significant differences were determined in each group regarding differences in circumference of the two legs at the thigh and calf levels and the visual analogue scale (VAS) of pain, and in groups B, C, and D regarding the Lowenberg test for diseased and healthy legs (p < 0.001). Between days 0 and 7, significant differences were found in the superficial femoral artery, superficial femoral vein, femoral vein, and the popliteal vein within groups A and D (p < 0.05). Conclusions: Traditional management, sc administration of low-molecular-weight heparin, and pneumatic compression of patients with DVT led to a faster reduction of leg swelling and pain and to increased volume flow through the deep veins of the legs.
Keywords: deep vein thrombosis; pneumatic compression; venous outflow; color Doppler sonography